Implementasi Hukum Adat To Cerekang dalam Pelestarian Sumber Daya Alam di Desa Manurung Kecamatan Malili Kabupaten Luwu Timur - S, Samiyem; H, Hasriyanti; M, Maddatuang (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the implementation of To Cerekang customary law in the preservation of natural resources in Manurung Village, Malili District, East Luwu County. Research objectives include forms of customary law implementation, factors supporting and hindering the implementation of customary law, as well as community perceptions and participation towards natural resource preservation and its impact on environmental sustainability. The research method used was qualitative with a case study approach, involving in-depth interviews, participatory observation, and documentation. The study results show that the implementation of customary law To Cerekang is realized through regular patrolling, installation of customary territory boundary markers, education and socialization of customary values, enforcement of customary sanctions, as well as village government support. Key supporting factors are the formal recognition of local governments, the active participation of indigenous peoples, and the involvement of the younger generation. Meanwhile, inhibiting factors include the as yet no recognition of customary law nationally, as well as potential land conflicts with the mining company’s side. Community perceptions of customary law are very positive and active participation of communities in the preservation of natural resources impacts on the sustainability of a well-maintained environment. The study concludes that To Cerekang customary law plays an important role as an effective and sustainable local wisdom-based natural resource conservation instrument.